Feeding Pasteurized Waste Milk to Preweaned Dairy Calves Changes Fecal and Upper Respiratory Tract Microbiota - Maynou, Georgina; Chester-Jones, Hugh; Bach, Alex; Terré, Marta (Frontiers in Veterinary Science, 2019)
ABSTRACT In the present study bacterial communities from both, the gastrointestinal and respiratory tract of pre-weaned dairy calves fed two different milk-feeding programs were characterized using 16S rRNA gene sequencing. Twenty female Holstein calves (38.8 ± 1.40 kg of BW) were fed pasteurized waste milk (pWM) containing residues of various antimicrobials. Twenty additional calves (38.1 ±1.19 kg of BW) were fed milk replacer (MR) with similar nutrient composition (27.5% crude protein, 32.1% fat) compared to waste milk (28.6% crude protein, 30.0% fat) from day 1 to weaning at day 49 of study. Fecal samples and nasal swabs were collected on day 42 only from calves that were not treated with therapeutic antibiotics throughout the study, which were 8 MR and 10 pWM calves. To assess the impact of the two feeding regimes on the fecal and nasal microbiota, α and β-diversity measures were calculated, and the relative abundance of operational taxonomic units (OTUs) at different taxonomic levels was determined for each sample. In general, Chao1, PD Whole Tree, and Shannon diversity indices were similar for the fecal and nasal bacterial communities of calves regardless of the feeding regime. However, principal coordinate analysis based on unweighted Unifrac distances indicated differences in the structure of bacterial communities of calves fed milk replacer compared with those from calves fed pasteurized waste milk. The relative abundance of the Streptococcaceae family and the genus Histophilus was greater (P < 0.05) in the nasal microbiota of calves fed milk replacer than in those fed pasteurized waste milk. However, the genus Prevotella tended (P = 0.06) to be more relatively abundant in the respiratory tract of calves fed pasteurized waste milk than in those fed milk replacer. Differences in relative abundances of bacterial taxa in gut microbiota were only observed at the phylum level, suggesting that antimicrobial residues present in waste milk have a non-specific influence at a lower taxonomical level.